Experimental study on lightweight concrete using Leca, silica fume, and limestone as aggregates. (2022) - Karthik, J.; Surendra, H.J.; Prathibha, V.S.; Anand Kumar, G.
Abstract: This article determines the mix proportions of high-strength structural lightweight concrete (HSSLWC), which uses expanded aggregate clay to decrease the weight of the concrete (LECA). Mineral and chemical admixtures have been used to reduce porosity and enhance strength in order to create HSSLWC. On the specimens, specific gravity, compressive, indirect tensile, and flexural strengths were determined. By exposing certain specimens to air, the impact of curing on compressive strength was studied. The findings indicate that by including Leca, a lightweight structural concrete (LWSC) with a dry density of 1, 600–1, 960 kg/m3 and a compressive strength of 35–66 MPa may be produced, based on cube specimens with a 100mmside length. When used with lightweight particles, limestone significantly improved the mechanical characteristics of concrete.